Overcoming Limitations for Research During the COVID-19 Pandemic via the Communicative Methodology: The Case of Homelessness During the Spanish Home Confinement. (29th September 2021) - Racionero-Plaza, Sandra; Vidu, Ana; Diez-Palomar, Javier; Gutierrez Fernandez, Nerea
Research on homelessness is a field of study in social sciences with a long and solid history. Several pieces of research have let us understand the life experiences and trajectories of these individuals, the challenges that they have faced, and the interventions conducted with them to address this inequality. Nonetheless, the research methodologies in those studies prove short in a situation such as the current COVID-19 pandemic. If we, researchers, are to prioritize social impact, we cannot wait for the pandemic to be overcome to employ those methodologies to investigate homelessness. If so doing, we would meet the needs of homeless people too late. Because social impact is at the forefront, if those methodological resources are not sufficient, then it is necessary to introduce additional ones. This article presents how to address this challenge via the employment of the communicative methodology of research, with the example of a qualitative investigation on how homeless people were attended during the lockdown in Spain in March 2020. The researchers could not meet these individuals on the streets by that time, yet their experiences during the lockdown and how they were being transformed were examined via on-line interviews with individuals voluntarily serving homeless people during home confinement. This methodological innovation in qualitative research is at the service of social impact and can be helpful to researchers investigating vulnerable groups in difficult times.